Surface morphology and structure of nanocrystalline diamond films deposited in CH₄/H₂/Ar glow discharge plasma - Vyrovets, I.I.; Gritsyna, V.I.; Dudnik, S.F.; Opalev, O.A.; Reshetnyak, E.N.; Strel'nitskiy, V.E. (Functional Materials, 2009)
Diamond films of up to 12 μm thickness have been deposited onto single crystal silicon substrates by CVD method in CH₄/H₂/Ar glow discharge plasma stabilized by magnetic field. X-ray diffraction analysis and atomic force microscopy have shown the films consist of about 1 μm in diameter conglomerates of 30-40 nm average size diamond nanocrystals. The conglomerate size increases by a factor of 2 as the film thickness grows from 1.7 up to 11.7 μm. At the same time, the nanocrystallite size remains essentially unchanged. In the diamond films, texture, compressive residual stresses and high concentration of crystal structure defects have been revealed.